The Integration of TPACK Framework in Field Experience Assessment Instruments for Pre-Service English Teachers in Indonesia - Syifa Fadhilah Hamid; Andri Kurniawan; Isnaniah Isnaniah (English Language in Focus (ELIF), 2023)
The effective use of technology in teaching process relies on the ability of teachers to develop knowledge using various technologies which appropriate to their content and pedagogical skills (Mouza, 2016). This knowledge is amalgamated into a framework called TPACK (Technology, Pedagogy, Content, Knowledge) which teachers have widely used to develop effective teaching using technology. Thus, this framework is used to assess pre-service teachers in global practices of educational context. Hence, this study aimed to explore the extent to which TPACK frameworks are integrated into the field experience assessment instruments in Indonesia. A qualitative content analysis research method and design were used in this study. There are 70 formulated indicators used to analyze the data (statements: words, phrases, and sentences). Data source of this study was 6 assessment instruments of field experience practice from 6 different universities around Indonesia. The result found that 27 out of 70 indicators were integrated into all components of the assessment instrument: Teaching Practice, Lesson Planning, Social Competence, Personality Competence, and Implementation Report. The domain of TPACK that integrated the most is Pedagogical Competence (PK). In contrast, none of the TCK and TPCK domain indicators were integrated into the field experience assessment components of pre-service English teachers in Indonesia.